Cultivating Educational Spaces that Support Black Girl's Spatial Inquiries. Issue 1 (1st March 2022) - Newhouse, Katie Scott
Abstract: In this article, I use data collected as part of my dissertation (Newhouse 2020 ) to inquire into how one participant, Joanna, who self-identifies as a Black girl, described her lived experiences while attending the Voices alternative-to-detention program. I use the theoretical framework of disability studies in education and critical race theory (DisCrit) with critical spatial theory to analyze collected ethnographic data, such as in-depth field notes, audio-recorded informal conversations, and semi-structured interviews, to show the space Joanna co-created with adult facilitators to center her lived experiences. An attention to the spatial dimension shows how spaces are agentive and has important implications for developing and sustaining educational spaces that cultivate an understanding of the geographies that draw from and center Black girls' lived experiences.